Revealing the propaganda of communication between the Islamic fundamentalism activists of the Middle East and Indonesia - Istadiyantha, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study reviews issues mainly related to propaganda strategies through media and the transmission of messages sustaining the Islamic fundamentalism activists’ agenda in the Middle East and Indonesia. Media plays a significant role in supporting the Muslim fundamentalists’ activities in both the Middle Eastern regional areas to the Asiatic countries, including Indonesia. This is an attempt to discover the underlying psycho-religious-social factors in the Islamic group of Radical-Fundamentalist Movements. This is completed by using a technical model of inductive thinking through exposing the collected data and the previous study results to draw general conclusion under the socio-religious psychology perspective of Peter Neumann as the analytical approach to reveal common underlying factors of people committing radical acts. The phenomenon of radical terrorist trips from the Middle Eastern countries to Indonesia, the occurring radicalization both in different regional areas has never undergone linear process, even tend to be a complex phenomenon. Through Internet media propaganda, Islamic radical-fundamentalist groups have been able to draw the sympathy of Muslims from various countries to jointly carry out jihad. Fundamentalist groups such as al-Qaeda and ISIS, proved to be no longer just local movements in Iraq and Syria, but have turned to be transnational movements. In the process of radicalization, the internet successfully facilitates the Muslim fundamentalist groups to transmitting and developing various narratives on religious life enjoyment under the auspices of the Khilafah which apply a single Islamic law-based state, in addition to position the Western countries as the real enemy to be fought.